Immune and hormonal activity in adults suffering from depression - Nunes,S.O.V. (2002)
An association between depression and altered immune and hormonal systems has been suggested by the results of many studies. In the present study we carried out immune and hormonal measurements in 40 non-medicated, ambulatory adult patients with depression determined by CID-10 criteria and compared with 34 healthy nondepressed subjects. The severity of the condition was determined with the Hamilton Depression Rating Scale. Of 40 depressed patients, 31 had very severe and 9 severe or moderate depression, 29 (72.5%) were females and 11 (27.5%) were males (2.6:1 ratio). The results revealed a significant reduction of albumin and elevation of alpha-1, alpha-2 and ß-globulins, and soluble IL-2 receptor in patients with depression compared to the values obtained for nondepressed subjects (P<0.05). The decrease lymphocyte proliferation in response to a mitogen was significantly lower in severely or moderately depressed patients when compared to control (P<0.05). These data confirm the immunological disturbance of acute phase proteins and cellular immune response in patients with depression. Other results may be explained by a variety of interacting factors such as number of patients, age, sex, and the nature, severity and/or duration of depression. Thus, the data obtained should be interpreted with caution and the precise clinical relevance of these findings requires further investigation.